Pengaruh Laba Akuntansi, Kinerja Keuangan, dan Struktur Modal terhadap Return Saham - Nur Chaeriyah; Ita Darsita (Excellent, 2026)
This research aims to determine and analyze the effect of Accounting Profit, Financial Performance, and Capital Structure on Stock Returns. The object of this research is the Consumer Non-Cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 period. This sector was selected due to its defensive and stable characteristics in producing basic consumer goods, with a demand level that is inelastic to economic cycle fluctuations. This research is a quantitative study utilizing an associative method. The data used are secondary data obtained from the official annual financial reports published by the respective companies. The sample was selected using the purposive sampling method. The data analysis technique employed is panel data regression analysis, processed using Microsoft Excel and EViews 14 software. The results of this research indicate that simultaneously, Accounting Profit, Financial Performance, and Capital Structure have an effect on Stock Returns. However, partially, Accounting Profit and Financial Performance have no effect on Stock Returns, whereas Capital Structure partially affects Stock Returns.